Diplomasi Kebudayaan Korea Selatan di Indonesia Melalui Komunitas Sahabat Korea Tahun 2019-2021 - Zulfian, Muhammad Haekal (GLOBAL INSIGHT JOURNAL, 2024)
This journal explores South Korean cultural diplomacy in Indonesia during the years 2019-2021, focusing on the role played by the "Sahabat Korea" community. Analyzing the initiatives, events, and collaborations within this cultural exchange platform provides insights into the strategies employed by South Korea to enhance bilateral relations and foster mutual understanding between the two nations. The study sheds light on the impact of cultural diplomacy facilitated by grassroots communities and its significance in shaping diplomatic discourse.